Cuestionarios de atención espiritual en cuidados paliativos: revisión de la evidencia para su aplicación clínica - Oliver, Amparo; Benito, Enric; Sansó, Noemí; Galiana, Laura (Psicooncología, 2017)
Objective: review of the more recent questionnaires assessing spiritual needs and resources in palliative care, and determine their clinical applicability in our environment.Methods: systematic review, following PRISMA guidelines, of all publications about spirituality appeared on 2015-2016. Papers had to be focused on spiritual care or spirituality assessment, based on a palliative care population, and gone through a peer review.Results: a total of 42 publications were identified, but after the evaluation of two independent observers, only 15 fulfilled the selection criteria. The selected papers were analyzed according to their characteristics, psychometric properties and applicability.Conclusions: the need of improving spiritual care in the dying process lead to the advent of many assessment and spiritual care tools. Their use has to be considered together with the clinician experience, their applicability on the cultural context and their psychometric properties.
Keywords: Palliative care; spirituality; outcome measures; psychometric properties; spiritual care.